HEAT CONDUCTION PROBLEM IN A THERMAL BARRIER COATING USING ANALYTICAL AND NUMERICAL APPROACH - Ahsani Ummi, Maharani
Nowadays, the application of Thermal Barrier Coating (TBC) has been increased dramatically in various industries due to these coatings can extend part life of components by reducing thermal fatigue. TBC is commonly used to protect machine components from the high-temperature surroundings, a condition which commonly occurs in nuclear reactors, turbine blade in airplanes, etc. TBC serves to maximize the utilization of component’s lives by insulating the components from high temperatures exposure. One way to create an appreciable temperature difference between the components and the coating surface is by determining the optimum thickness of the TBC that usually done by experiments. However, conducting experiments are expensive and time-consuming. Therefore, a computer simulation is needed to overcome these problems. This study aims to develop a computer simulation based on finite element method. Furthermore, we present the analytical solution of a simple mathematical TBCs model derived from Laplace transformation and Residue theorem. Then, we test the accuracy of the simulation by comparing the simulation results with the analytical solution. The result shows that both of the simulations based on finite element method and the exact solution are in agreement which confirm the accuracy of the model/simulation